Diarrhea hospitalization costs among children <5 years old in Madagascar. Issue 47 (3rd November 2020) - Burnett, Eleanor; Rahajamanana, Vonintsoa Lalaina; Raboba, Julia Liliane; Weldegebriel, Goitom; Vuo Masembe, Yolande; Mwenda, Jason M.; Parashar, Umesh D.; Tate, Jacqueline E.; Robinson, Annick Lalaina
Abstract: Background: Following a recommendation by the World Health Organization, Madagascar introduced rotavirus vaccine in 2014. Though national rotavirus vaccine coverage has remained <80%, rotavirus hospitalizations declined by 78%. Gavi, the Vaccine Alliance, has provided financial support for rotavirus vaccine, however the Malagasy government has increasing responsibility for the financial cost. Methods: In this evaluation, we describe the direct medical, direct non-medical, and indirect cost of illness due to diarrhea among children <5 years old at a public pediatric referral hospital. A 3-part structured questionnaire was administered during and following the hospitalization and the child's hospital record was reviewed. Results: In total, 96 children were included in this analysis. The median total cost of the illness was $156.00 (IQR: 104.00, 210.86) and the median direct medical cost was $107.22. Service delivery costs represented a median of 44% of the inpatient costs; medications and diagnostic tests represented a median of 28% and 20% of the total costs of the hospitalization, respectively. The median percentage of the total illness costs paid by the household was 67%. Among households with income of <$61/month, the median costs of the illness paid by the household were $78.55, representing a median of 168% of the household's monthly expenses. Among households earning >$303/month, the median costs paid by the household were $147.30, representing a median of 53% of the household's monthly expenses. Among all household income levels, caregivers commonly paid these bills from savings, borrowed money, and donations. Conclusions: Our findings will be useful in assessing the cost-effectiveness of rotavirus vaccine by decisionmakers. These results may also help hospital administrators and healthcare providers better understand the financial constraints of families.